Living Quran di Era Digital: Analisis Praktik Tadarus Online Selama Ramadhan pada Platform Internet: Penelitian - Lu’luatul Fauziah; Altaf Abdurrohman; Hikmatul Lutfi (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
In today's digital era, the practice of reciting the Qur'an has undergone a significant transformation, thanks to the presence of various online platforms that make it easier for Muslims to engage in worship through reading the Qur'an, especially during the month of Ramadan. This study analyzes how online tafsir on internet platforms becomes part of the